STRENGTHENING THE HINDU'S RELIGIOUS VALUES ON MILLENNIAL HINDU GENERATION TO - Ni Putu Suwardani (IAHN-TP Palangka Raya, 2019)
The radicalism act in Indonesia in the name of religion has captured the attention of many parties. Radicalism is contrary to religious values. This situation is disturbing for the general public and millennial generation. The millennial generation is seen as a potential unifier of the nation but also very vulnerable to introduced and as a group to spread radicalism. Their access to digital information is very high. Unfortunately, not all information they received is entirely correct; they often exposed by content that full of intolerance, and hatred that is contrary to the values of religion and national civilization. Their vulnerability to be disclosed by radicalism ideology was caused due to lack of understanding in the religious values that teach peace (santih), the importance of brotherhood (Vasudaiva Kutumbhakam, Tat Twam Asi), as well as other virtue values. Digital technology that used wisely can raise social, cultural, and religious vulnerabilities. This paper is a synthesis of thought with a library research approach to explore opinions and findings to formulate new ideas as a response to the challenges and opportunities of millennial Hindu generations in the era of digital technology. Two important things that must be done to the millennial Hindu generation are strengthening the values of peace and brotherhood and also improves and carrying out the teachings of dharma.